Developing of Chemically Treated Waste Biomass Adsorbent for Dye Removal - Asim N.; Amin M.H.; Alghoul M.A.; Sulaiman S.N.A.; Razali H.; Akhtaruzzaman M.; Amin N.; Sopian K. (Bellwether Publishing, Ltd., 2023)
Adsorbents; Aromatic compounds; Biomass; Fourier transform infrared spectroscopy; Scanning electron microscopy; Waste treatment; X ray photoelectron spectroscopy; Chemical treatments; Coconut coirs; Dye removal; Experimental factors; Fourier transform infra red (FTIR) spectroscopy; Methylene Blue; Moisture absorbency; Waste biomass; Thermogravimetric analysis; Adsorbents; Aromatic Compounds; Biomass; Effluent Treatment; Esca; Gravimetry; Scanning Electron Microscopy; Thermal Analysis; X Ray Spectroscopy